Analysis of Cultural Geography Learning Concept Design Based on Case Method and Team-Based Project - Rahmadi, M Taufik; ., Sugiharto; Lubis, Darwin Parlaungan; Lukitoyo, Pristi Suhendro; Halim, Jennifer (KnE Social Sciences, 2024)
Since the issuance of the Service of Instruction and Culture Proclaim No. 3/M /2021 in 2021 concerning Key Execution Pointers (IKU), where classroom learning will utilize one or a combination of the case strategy and project-based gather learning (team-based venture), which incorporates 50% in its assessment weight. Hence, this investigation pointed to plan learning concepts in political geology courses with a case strategy method and team-based venture within the Division of Geology Instruction, Workforce of Social Sciences, Medan State College. This inquiry about employment uses an expressive, subjective approach. The populace in this were all 454 understudies of the Division of Topography Instruction for the 2020-2022 year, and the test was 67 understudies. Information collection employs a survey (survey) disseminated to understudies through Google Shapes. This consideration demonstrates that executing case strategy and team-based project-based learning got a positive reaction from understudies. Based on the overview, 87% of understudies concurred that the schedule assignment task framework in papers was supplanted with dialogue learning by watching and analyzing various phenomena or issues within the environment or standard of living. Then, 76% of understudies concurred in case the assignments within the shape of CBR and CJR, and within the IQF learning framework were supplanted with the substance of hypothetical thinking in case of strategy reports and team-based projects. Selection of case strategies and team-based ventures carried out in bunches by groups by raising case considers that happen around or in the standard of living. Besides, the examination will be displayed and talked about in the course on the other hand. Keywords: geography learning, design, case method, team-based project